Chemical Composition and Nutritional Information of Fats Used in Fillings of Sandwich Cookies. (4th July 2019) - da Silva, Thais Lomonaco Teodoro; Martini, Silvana; Arellano, Daniel Barrera
Abstract: The aim of this work was to evaluate the characteristics of fillings used in cookies commercialized in Brazil and in USA according to their chemical composition, labels, nutritional information, ingredients list, and price. Fillings had approximately 25–32% of fat. In general, the composition of these fats consisted of approximately 50% of saturated fatty acids (SFA), mainly palmitic acid, and 50% of unsaturated fatty acids, mainly oleic acid. Brazilian samples had trans ‐fatty acids (TFA) in the range of 1–15% although in many cases their presence was not reported in the labels. USA product labels did not present a fixed portion weight but they showed detailed information about the types of fats used such as source and the process used for their production. In 70% of Brazilian product labels, the information shown in the ingredient list was limited to "vegetable fat, " which does not give enough information to consumers about the type of fat used. In addition, our results showed that low‐ trans ‐products or zero‐ trans ‐products, in which TFA were replaced by SFA, presented the highest prices. This research suggests that further legislation should be developed in Brazil to decrease the amount of TFA in foods and improve their nutritional properties.